2016
DOI: 10.1007/s00261-016-0921-6
|View full text |Cite
|
Sign up to set email alerts
|

Impact of hepatobiliary phase liver MRI versus Contrast-Enhanced Ultrasound after an inconclusive extracellular gadolinium-based contrast-enhanced MRI for the diagnosis of benign hepatocellular tumors

Abstract: HBP-MRI or CEUS should be performed after an inconclusive CE-MRI. Both can change patient management by avoiding unnecessary biopsy or surveillance. The use of HBP-MRI should be advocated over CEUS in larger (>35 mm) lesions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 39 publications
1
7
0
1
Order By: Relevance
“…We observed that HT expression in FNH is characterized by a periseptal pattern, with little variation in different cases, matching the iso/hyperintense contrast uptake on the HBP of Gd‐EOB‐DTPA‐enhanced MRI that is consistently reported in the literature . By contrast, in HCA, HT expression is heterogeneous, resulting in a variable intracellular uptake of the hepatospecific contrast agent .…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations
“…We observed that HT expression in FNH is characterized by a periseptal pattern, with little variation in different cases, matching the iso/hyperintense contrast uptake on the HBP of Gd‐EOB‐DTPA‐enhanced MRI that is consistently reported in the literature . By contrast, in HCA, HT expression is heterogeneous, resulting in a variable intracellular uptake of the hepatospecific contrast agent .…”
Section: Discussionsupporting
confidence: 81%
“…We observed that HT expression in FNH is characterized by a periseptal pattern, with little variation in different cases, matching the iso/ hyperintense contrast uptake on the HBP of Gd-EOB-DTPA-enhanced MRI that is consistently reported in the literature. 24,25,27,30,32,34 By contrast, in HCA, HT expression is heterogeneous, resulting in a variable intracellular uptake of the hepatospecific contrast agent. 27 Our results refine those reported in a previous study, based on outdated pathological classifications, showing consistently low OATPB1/B3 mRNA levels and IHC expression in 9 HCA.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For CE‐MRI with hepatocellular specific contrast, the sensitivity is estimated at 91%–100% and the specificity at 87%–100% . When the diagnosis remains uncertain, these patients may undergo a tumor biopsy . In order to avoid a percutaneous biopsy and the associated risk of complications or even the surgical resection of a suspect lesion that turns out to be FNH, improvement of the diagnostic process is needed.…”
Section: Introductionmentioning
confidence: 99%